FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI LADA DI DESA KONGKOMOS KECAMATAN BASIDONDO KABUPATEN TOLITOLI - Fatmah Fatmah; Nur Hikmah; Usman (Jurnal Agrotech, 2020)
This study aims to determine the factors that influence production and the magnitude of the factors that affect the production of Pepper in Kongkomos Village, Basidondo District, Tolitoli Regency. The time of research and data collection was carried out from October to November 2018. The determination of the purpose and location was determined intentionally, based on the consideration that Kongkomos Village had the highest production in Tolidoli, Basidondo Regency. The results showed that the factors influencing Pepper Farming Production were variable land area (X1), pesticides (X2), urea fertilizer (X3) and labor (X4). Variable X (land area, pesticides, urea fertilizer and labor) simultaneously has a significant effect on the Y variable (pepper production) with a value of R2 = 0.97, which explains that the contribution of variable X (land area, perticide, urea fertilizer, labor) ) to increase the fall of the variable Y (pepper production) by 97% while the remaining 3% is caused by other factors outside the production function model analyzed. From the results of the persial test it was revealed that the variables X1 (land area) 2,968, X2 (pesticides) 2,817, X3 (urea fertilizer) 4,488 and X4 (labor) 3,104 were greater than the value of t-table 2.78 which meant that the variable X1 (area land)), X2 (pesticides), X3 (urea fertilizer) and X4 (labor) have a significant effect on pepper production.